2007
DOI: 10.1111/j.1468-2982.2007.01357.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of The Remote C Fibres Stimulation Induced by Capsaicin on the Blink Reflex in Chronic Migraine

Abstract: The aim of this study was to test the function of the diffuse noxious inhibitory control system (DNIC) in chronic and episodic migraine, exploring the blink reflex (BR) modifications induced by topical application of capsaicin on the hand. We evaluated 11 migraine without aura (MA) and nine chronic migraine (CM) patients during the not symptomatic phase; they were compared with 14 non-headache subjects (N). The BR was elicited by weak electrical stimuli delivered to the right supraorbital nerve; it was obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 28 publications
5
59
0
Order By: Relevance
“…The controls and migraineurs without aura did not exhibit any reflex alterations. These results may suggest a failure of the diffuse noxious inhibitory control system and a disturbed control of the trigeminal reflex at the central level, linked with migraine frequency (De Tommaso et al 2007). …”
Section: Blink Reflexmentioning
confidence: 96%
“…The controls and migraineurs without aura did not exhibit any reflex alterations. These results may suggest a failure of the diffuse noxious inhibitory control system and a disturbed control of the trigeminal reflex at the central level, linked with migraine frequency (De Tommaso et al 2007). …”
Section: Blink Reflexmentioning
confidence: 96%
“…In line with this, Sandrini et al (2006) found CPM dysfunction in patients suffering from migraine. Likewise, Tommaso et al (2007) also found CPM dysfunction in chronic migraineurs; however, patients with more episodic migraine without aura did not show this deficit. Interestingly, Perrotta et al (2010) also found no CPM dysfunction in patients with episodic migraine compared with healthy controls (CPM deficits were apparent only in patients with medication-overuse headache).…”
Section: Introductionmentioning
confidence: 96%
“…TRPV1 is expressed by keratinocytes in the epidermis as well as by fibroblasts, endothelial cells and immunocompetent cells in the dermis [7,14]. However, of main relevance in the context of analgesic effects is the anatomic fitting of the skin layers especially with C and Aδ pain fibres, which are established in the dermis but grow into the vital epidermis [59,60]. With regard to an optimized bioavailability of capsaicin, the mean effect concentration (EC 50 ) at mechanoheat-sensitive C fibres of approximately 350 nmol/l as well as toxicological in vitro data about apoptosis induction at >5 µmol/l over 6 h for keratinocytes and >5 µmol/l over 24 h for cutaneous fibroblasts need to be considered [10,61,62].…”
Section: Discussionmentioning
confidence: 99%